2022
DOI: 10.3390/su14074064
|View full text |Cite
|
Sign up to set email alerts
|

Fish Feeds in Aquaponics and Beyond: A Novel Concept to Evaluate Protein Sources in Diets for Circular Multitrophic Food Production Systems

Abstract: With the general objective of optimizing internal nutrient recycling, circular multitrophic food production systems, e.g., combining fish, plant, and insect larvae production, rely on the quality and composition of sustainable nutritional inputs. Therefore, differences in dissolved and solid nutrient excretion patterns produced by Nile tilapia (Oreochromis niloticus) reared in recirculating aquaculture systems (RAS) with 5% daily water exchange and fed black soldier fly meal (BSFM), poultry by-product meal (PM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
39
1

Year Published

2022
2022
2025
2025

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(52 citation statements)
references
References 102 publications
12
39
1
Order By: Relevance
“…The highest food conversion ratio was observed in the fry feeds with Diet 2 crude protein with the value of 0.32 ± 0.57 cumulative. The other feeds 30%, 35% and 45% crude protein recorded 0.25 ± 0.04, 0.32 ± 0.57 and 0.25 ± 0.04 respectively which were similar to [43]. The highest cumulative gross food conversion efficiency was recorded in the fry fed with 532.14 ± 131.12 and the lowest gross food conversion efficiency was recorded in fry fed with 35% crude protein with the value of 412.48 ±105.57 corresponding to the observations of [41,42].…”
Section: Discussionsupporting
confidence: 75%
“…The highest food conversion ratio was observed in the fry feeds with Diet 2 crude protein with the value of 0.32 ± 0.57 cumulative. The other feeds 30%, 35% and 45% crude protein recorded 0.25 ± 0.04, 0.32 ± 0.57 and 0.25 ± 0.04 respectively which were similar to [43]. The highest cumulative gross food conversion efficiency was recorded in the fry fed with 532.14 ± 131.12 and the lowest gross food conversion efficiency was recorded in fry fed with 35% crude protein with the value of 412.48 ±105.57 corresponding to the observations of [41,42].…”
Section: Discussionsupporting
confidence: 75%
“…The enormous amount of valuable protein that could be extracted [ 1 , 2 , 3 , 4 , 5 ] (about 30–40% of the total weight), is one of the most appealing aspects of seafood by-products. More than 20 million tons of them are produced annually from the fish tissues that are discarded as waste, including fins, heads, skin, and viscera [ 6 , 7 , 8 ]. Because of their elevated protein content, absence of disease transmission risks, high bioactivity, and less considerable religious and ethical restrictions, the use of fish by-products as a new source of collagen has drawn increasing attention [ 9 , 10 , 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…This study cannot convincingly ascertain whether feed uptake was higher in aquaponics, but this is likely to be the case. Studies have reported better feed conversion efficiency in Nile tilapia raised in aquaponics than in those raised in conventional fishponds (Amin et al, 2021; Shaw et al, 2022; Strand et al, 2007). An important observation in the aquaponic fish tank was the presence of slimy cyanobacteria (Figure 5), which increased with time and has been reported to significantly contribute to more than 10% of fish protein intake and affect their gut microbiome(Rosenau et al, 2021).…”
Section: Discussionmentioning
confidence: 99%